Contribution of Murine Models to the Study of Malaria During Pregnancy - Barateiro, André; Pereira, Marcelo L. M.; Epiphanio, Sabrina; Marinho, Claudio R. F. (Frontiers in Microbiology, 2019)
Annually, many pregnancies occur in areas of Plasmodium spp. transmission, particularly in underdeveloped countries with widespread poverty. Estimations have suggested that several million women are at risk of developing malaria during pregnancy. In particular cases, systemic infection caused by Plasmodium spp. may extend to the placenta, dysregulating local homeostasis and promoting the onset of placental malaria; these processes are often associated with increased maternal and fetal mortality, intrauterine growth restriction, preterm delivery, and reduced birth weight. The endeavor to understand and characterize the mechanisms underlying disease onset and placental pathology face several ethical and logistical obstacles due to explicit difficulties in assessing human gestation and biological material. Consequently, the advent of murine experimental models for the study of malaria during pregnancy has substantially contributed to our understanding of this complex pathology. Herein, we summarize research conducted during recent decades using murine models of malaria during pregnancy and highlight the most relevant findings, as well as discuss similarities to humans and the translational capacity of achieved results.